TAKOTSUBO CARDIOMYOPATHY AND THE HEART-BRAIN AXIS - Fillipe Bispo de Oliveira, Estevan; Pedro do Valle Varela, João; Alves Liphaus, Luiza; Batista Rosado, Álvaro; Miranda Nobre, Julia; Alves Brambilla, Bernardo; Luiza Ferraz Barbosa, Ana; Cypreste Preti, Letícia; de Oliveira Figueiredo, Bruno; de Figueiredo Moutinho, Bruno; Moraes dos Santos, Gabriel; Rocha Santório, Éric; et al. (Health and Society, 2025)
Takotsubo cardiomyopathy (TC), also known as broken heart syndrome, is a transient heart condition often triggered by intense emotional or physical stress. It is characterized by temporary ventricular dysfunction that mimics acute coronary syndrome, but without significant obstruction of the coronary arteries. Recent studies indicate a strong connection between the central nervous system and the heart, known as the heart-brain axis, which influences the pathophysiology of TC. This study seeks to explore the relationship between Takotsubo cardiomyopathy and the heart-brain axis, evaluating the neurocardiogenic mechanisms involved and their clinical implications for the diagnosis, prognosis and management of the disease. This is a bibliographic review with a qualitative approach, using the PubMed, Scopus and Web of Science databases to search for scientific articles. Specific descriptors related to Takotsubo Syndrome and its relationship with neurocardiological and psychological aspects were used to refine the search. The time frame covers the years 2020 to 2023, according to the date of the first and last reference selected. Takotsubo cardiomyopathy is strongly associated with hyperactivation of the sympathetic nervous system and excessive release of catecholamines, leading to transient myocardial dysfunction. The heart-brain axis plays a crucial role, as evidenced by neuroimaging studies that show alterations in brain regions responsible for emotional processing, such as the amygdala and prefrontal cortex. In addition, patients with TC have a higher prevalence of psychiatric disorders such as anxiety and depression, suggesting a bidirectional interaction between the brain and the heart. The management of TC involves hemodynamic support and stress control, with an increasing focus on neurocardiological approaches. Takotsubo cardiomyopathy exemplifies the complex interaction between the brain and the heart, reinforcing the need for a multidisciplinary approach in its diagnosis and treatment. The study of the heart-brain axis opens up new perspectives for understanding the neurocardiogenic mechanisms of the disease and may contribute to more effective therapeutic strategies, preventing recurrences and improving patient prognosis.